Hepatoprotective activities of polyherbal formulations: A systematic review - Elizabeth B. Aladejana; Adebowale E. Aladejana (AOSIS, 2023)
Background: Liver diseases pose a substantial global public health challenge, encompassing conditions such as liver failure, hepatitis, cirrhosis and associated complications Safeguarding the liver becomes important as these conditions impact human health. Hepatoprotective agents play a pivotal role in mitigating liver damage caused by chemicals, drugs and toxins. Polyherbal formulations, combining botanical components from traditional medicine, offer a promising approach to addressing liver disorders. Their popularity arises from a multi-targeted strategy in treating complex diseases, marking a shift in focus toward these formulations. Aim: The study aimed to conduct a thorough review of the existing literature on the hepatoprotective activity of polyherbal formulations and provide a comprehensive overview of their mechanisms of action. This review provides the overview of the use of polyherbal formulations in the management of liver disease. Method: A systematic search of electronic databases, including : Scopus, Academia, Elsevier, Science Direct, Wiley, BioMed Central, PubMed, and Google Scholar, was conducted using a combination of keywords such as 'polyherbal formulations', 'hepatoprotective' and 'liver diseases'. Studies published between January 2010 and April 2023 were included in the review. Results: A total of 61 articles were reviewed, and the studies showed that polyherbal formulations possess significant hepatoprotective activity against various hepatotoxic agents. The mechanisms of action of these formulations include antioxidant, antiinflammatory, antifibrotic and antiapoptotic effects. Additionally, some polyherbal formulations were found to stimulate liver regeneration, enhance bile secretion and promote detoxification processes. Conclusion: Polyherbal formulations have shown promising hepatoprotective activity, and their multitargeted approach to treating complex diseases makes them a potential alternative to conventional medicines. However, identifying the active compounds responsible for the hepatoprotective effects of these formulations and their pharmacokinetics and pharmacodynamics could provide insights into the development of new and effective drugs for liver disorders. Contribution: This article contributes to the growing body of literature on the potential of polyherbal formulations as hepatoprotective agents.